South Sudanese refugee Women's healthcare access and use: An integrative review - Elizabeth O. Okegbile; Mellissa M. Goldsmith; Janice D. Crist (Elsevier, 2020)
Background: People who migrate and settle in new places encounter other people, different cultures, lifestyles, healthcare services and environments that create conditions that may impact their health in the course of their journey and during the transition to the new environment. Vulnerable populations such as refugees continue to face difficulty in navigating an ever more complex healthcare system in which resources are limited and barriers to healthcare services access are numerous. In the United States (U. S.), these barriers have been linked to the culture of refugee populations and the complexity of the healthcare system. South Sudanese women are an exemplar of a culturally unique vulnerable population with these barriers to healthcare services. Aim: The purpose of this integrative review was to examine published research reports on healthcare access and use by the South Sudanese refugee women who have settled in the United States, as well as their perceptions of the influence of their culture on their access and use of healthcare. Methods: Whittemore and Knafl's integrative review method guided this analysis. Results: Nine studies met the inclusion criteria (seven qualitative, two quantitative). Three main themes emerged from the review: Refugee Healthcare Access and Use, Refugee Women's Healthcare Access and Use, and Sudanese Refugee Women's Healthcare Access and Use. These themes confirm both women's knowledge gaps about healthcare as well as gaps in the literature regarding the healthcare access and use of the South Sudanese refugee women who have resettled in the U. S. Conclusions: This review discovered that there a is dearth of research literature about South Sudanese refugee women's healthcare access and use in relation to their cultural perspectives.